Azathioptrine in Refractory Tolosa-Hunt Syndrome: Two Case Report - Devi Ariani Sudibyo; Mohammad Saiful Ardhi (Universitas Airlangga, 2022)
Introduction: Tolosa-Hunt syndrome (THS) is an inflammatory disease with painful ophthalmoplegia and unilateral periorbital headache as detailed by the International Classification of Headache Disorders, 3rd edition (ICHD-3). Azathioprine has been suggested as a second-line treatment in refractory THS when oral corticosteroid only gives a partial response. Case: Two cases of THS, 45-year-old and 41-year-old women with unilateral headache, drooping of the left upper eyelid, and diplopia. They presented with complete ophthalmoplegia and ophthalmic division of trigeminal nerve disturbance. Magnetic resonance imaging (MRI) showed thickening of the left cavernous sinus, suggesting THS, while the other was normal. Corticosteroid (prednisone 1-1,5 mg/day) was given orally for the first two weeks, and according to the Numeric Pain Rating Scale (NPRS), pain intensity was reduced from severe to moderate. As a second-line treatment, azathioprine (2 mg/kg/day) was given afterward, with a significant reduction in pain intensity and remission of ophthalmoplegia within seven days. Azathioprine was used as an immunosuppressive agent and was continued for another three months without any deterioration in neurological deficits. The levels of complement 3, 4 (C3, C4), and C-reactive protein (CRP) were normal in both patients, with a slight increase in erythrocyte sedimentation rate (ESR) and equivocal values on antinuclear antibody (ANA) results. Other differentials of THS were eliminated from history-taking, physical examination, and proper investigations. Conclusion: Azathioprine as a second-line treatment can be used instead of an oral corticosteroid for refractory cases of THS with fewer side effects. Complete remission of ophthalmoplegia and a significant reduction in pain intensity was obtained.